An exploration of young South African Indian women’s lived experiences of the intergenerational transmission of trauma in the post-Apartheid context in Johannesburg - Sibanda, Sharon (University of Pretoria, 2023)
Mini Dissertation (MA (Counselling Psychology))--University of Pretoria, 2022.